2008
DOI: 10.4103/0019-5545.43630
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of personality disorder associated with deliberate self harm in two different age groups (15-24 years and 45-74 years)

Abstract: Aims:To study the presence of personality disorder in cases of deliberate self harm (DSH) in young (15–24 years) and elderly (45–74 years) and compare.Materials and Methods:Deliberate self harm cases admitted in Medical and surgical departments and cases attending psychiatry department of R.G. Kar Medical College, Kolkata were studied. For diagnosis of personality disorder ICD 10 International Personality Disorder Examination (IPDE) questionnaire was used.Results:Percentage of elderly patients having personali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 7 publications
2
19
0
Order By: Relevance
“…Nath et al . [ 25 ] made similar observation in their comparative study of personality disorder associated with DSH in two different age groups (15-24 years and 45-74 years). Sarkar et al .…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Nath et al . [ 25 ] made similar observation in their comparative study of personality disorder associated with DSH in two different age groups (15-24 years and 45-74 years). Sarkar et al .…”
Section: Discussionsupporting
confidence: 55%
“…Most of the Indian studies[ 18 19 20 21 22 23 24 25 26 ] focus on the sociodemographic and clinical profiles on DSH, and self-injurious behaviors are hospital-based either in general hospital psychiatric units or from consultation-liaison psychiatric unit. The present report is unique in that it is first of its reported from a government licensed private psychiatric institute and hospital from an urban area.…”
Section: Discussionmentioning
confidence: 99%
“…Chandrasekaran et al (2003) found that among 341 patients who attempted suicide, PD was identified only in 7%, with 0.58% cases of BPD and all suffered from a comorbid psychiatric illness. Nath et al (2008) aimed to identify the type of PD commonly associated with deliberate self-harm. It was found that the most common disorder was emotionally unstable (both borderline and impulsive type, 28.6%) in young females.…”
Section: Researches On Bpd In Indiamentioning
confidence: 99%
“…Data on the prevalence of PD among clinical populations in India are scarce with estimates ranging from 0.14 9 to 62.1%. 10 The existing data are largely derived from highly specialized clinical populations (e.g. those attending addiction services or who have recently attempted suicide).…”
Section: Introductionmentioning
confidence: 99%